Do unfair experiences contribute to anger and hostility in young children? : young children's perception of unfairness and its associated feelings : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology - Yamaguchi, Tomoko (Massey University, 2005)
Being able to cope in emotionally demanding situations is a necessary skill for both children and adults. Parents use many disciplinary techniques to help children manage their misbehaviour and overtly expressed negative emotions. Although numerous parenting strategies have been described by researchers and professionals, there are limited numbers of studies looking at aspects of disciplinary practices from young children's perspectives. By understanding children's affective responses to discipline practices, it is possible that parents can provide more effective help for their children, and reduce negative moods such as hostility. Based on Evans' model of the development of hostility, the present study investigated how young children's experiences of unfair treatment might influence their predominant affective expression or attitudes toward a parent who is being unfair. Thirty-two children, aged between five and nine years, were recruited from local primary schools and a summer holiday programme. Using a story about unfairness, the children were able to make judgements about the story and report feelings associated with such experiences. Three original tasks were introduced as an indirect measure of level of hostility in response to the experiences of unfair treatment. Although statistical analysis supported the hypotheses that hostility in children increases as a result of unfair experiences, judging from their verbal responses, there is a complex interactive effect of the mother-child relationship on children's feeling.
Keywords: Hostility (Psychology); Aggressiveness in children; Moral development; Reasoning in children; Interpersonal relations in children